Ketogenic diet–induced changes in methylation status and neuropeptide signaling: relationships between S-adenosylmethionine (AdoMet), orexin-A, and metabolic health - Mosca, Laura; Monda, Antonietta; Messina, Antonietta; Cadoni, Francesca; Moscatelli, Fiorenzo; La Marra, Marco; Monda, Vincenzo; Di Maio, Girolamo; Allocca, Salvatore; Casella, Claudia; Casillo, Maria; Polito, Rita; et al. (Frontiers in Physiology, 2025)
IntroductionS-Adenosylmethionine (AdoMet) is the principal methyl donor in numerous biochemical reactions, regulating lipid and glucose metabolism, inflammatory pathways, and neurotransmitter synthesis. Orexin-A, a hypothalamic neuropeptide involved in arousal, feeding behavior, and energy expenditure, plays a crucial role in metabolic homeostasis. Emerging evidence suggests potential crosstalk between methylation pathways and orexinergic signaling; however, this interaction has not been explored in the context of nutritional ketosis. This study aimed to evaluate the effects of a structured ketogenic dietary intervention on circulating AdoMet, Orexin-A, and key metabolic parameters.MethodsTwenty-one adults (11 males, 10 females) were recruited from the Unit of Dietetics, Sports Medicine, and Psychophysical Wellbeing, University Hospital “L. Vanvitelli” of Naples, Italy. Participants followed a ketogenic diet for 8 weeks. Anthropometric measurements, body composition, fasting biochemical parameters, AdoMet, and Orexin-A levels were assessed at baseline (T0) and post-intervention (T1). Paired t-tests were used to analyze within-subject changes, and linear regression analyses explored correlations between AdoMet and metabolic variables. The study was approved by the Ethics Committee of the University of Campania “Luigi Vanvitelli“ (Protocol No. 0003232/I, 01/02/2023).ResultsAfter 8 weeks, participants exhibited significant reductions in body weight, BMI, visceral adipose tissue, total cholesterol, fasting glycemia, triglycerides, and HbA1c (all p < 0.05). Circulating AdoMet (−75.7%) and Orexin-A (−7.2%) levels also decreased significantly. AdoMet levels positively correlated with body weight, BMI, visceral adipose tissue, total cholesterol, fasting glycemia, triglycerides, HbA1c, and notably Orexin-A (R2 = 0.3848, p < 0.0001).DiscussionThe ketogenic diet significantly improved anthropometric and metabolic parameters while concurrently reducing AdoMet and Orexin-A levels. The strong positive correlation between AdoMet and Orexin-A suggests an interaction between methylation status and neuropeptide signaling during metabolic adaptation to ketosis. These findings highlight AdoMet as a potential integrated biomarker of metabolic health and emphasize the relevance of neuro-metabolic regulation in dietary interventions.